Exploring Indonesian Undergraduate EFL Students’ Experiences of Online and Offline Peer Feedback in Argumentative Writing - Karisma Kurniawati (Faculty of Education and Teacher Training of UIN Palopo, 2026)
Writing is considered one of the most challenging skills to learn for English Foreign Learners (EFL). As a result, several students often face some problems and difficulties in writing. To solve their difficulties, the teacher and students need to apply a writing strategy that supports and helps the students in writing, such as peer feedback. This study aimed to explore the undergraduate students’ performance and quality of providing and receiving peer feedback. Then, it described their perceptions towards the offline and online peer feedback used while writing argumentative essays. This study used a qualitative interpretive study as the research design. To obtain the data, document analysis, and semi-structured interview were done by using students’ argumentative essay drafts, and interview question guidelines as the instruments. The participants of this study were 32 undergraduate students from two classes at one of the state universities in Surabaya. The results of this study showed that many changes in students' final argumentative essay drafts who used online peer feedback. Furthermore, based on the undergraduate students’ perception, peer feedback was beneficial, important, and effective to be used in writing argumentative essays. However, there were also some challenges faced by the students during the process. Luckily, they have their solutions to deal with those problems. In short, it can be concluded that peer feedback can be a good strategy that helps the students in writing.